Impact on quality-of-life: before and after topical combinational treatment in patients of acne vulgaris - Sehgal, Vijay K.; Kaur, Jasleen; Singh, Surinder Pal; Gupta, Anita K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective was to study quality-of-life in patients of acne vulgaris before and after treatment by benzoyl peroxide 2.5% gel and clindamycin 1% gel or benzoyl peroxide 2.5% gel and nadifloxacin 1% cream or tretinoin 0.025% and clindamycin 1% gel. Methods: This was a prospective, open, randomized, parallel comparative study of 60 patients of acne vulgaris attending the Department of Dermatology and Venereal Diseases, Government Medical College, Rajindra Hospital, Patiala. Three groups were made 20 in each group, one group received benzoyl peroxide 2.5% gel and clindamycin 1% gel, the second group received benzoyl peroxide 2.5% gel, and nadifloxacin 1% cream and the third group received tretinoin 0.025% and clindamycin 1% gel. Cardiff acne disability index questionnaire was filled before starting and after the treatment. Results: In these three groups, it was found that the group on benzoyl peroxide 2.5% gel and clindamycin 1% gel, mean score, before starting treatment was 8.35±3.48 and after treatment was 2.95±2.09 (p<0.001), group on benzoyl peroxide 2.5% gel and nadifloxacin 1% cream, mean score, before starting treatment was 7.60±3.75 and after treatment was 5.80±2.98 (p<0.001) and group on tretinoin 0.025% and clindamycin 1% gel mean score is 8.00±3.06 and after treatment was 5.40±2.93 (p<0.001). Conclusion: Quality-of-life improves more in patients taking benzoyl peroxide 2.5% gel and clindamycin 1% gel, and then, tretinoin 0.025% and clindamycin 1% gel and then benzoyl peroxide 2.5% gel and nadifloxacin 1% cream.